2010
DOI: 10.3748/wjg.v16.i2.251
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection rate and endoscopic changes after successful eradication ofHelicobacter pylori

Abstract: The reinfection rate in Korea is 9.1% which represents a decreasing trend. There was no relationship between H. pylori infection status and changes in endoscopic findings. There was also no recurrence or aggravation of ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The same study also reported that in areas of high prevalence of H. pylori, opportunities for horizontal transmission (from individuals outside the household) are higher. On the other hand, reinfection and recrudescence may occur after eradication therapy, supporting the acquisition of the bacteria during adulthood [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…The same study also reported that in areas of high prevalence of H. pylori, opportunities for horizontal transmission (from individuals outside the household) are higher. On the other hand, reinfection and recrudescence may occur after eradication therapy, supporting the acquisition of the bacteria during adulthood [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, many studies document persistence of H. pylori infection in the follow-up of patients even after appropriate treatment [11][12][13][14][15][16]. In our clinical team, the antibiotic protocol evolved according to successive guidelines, and remained based on a combination of amoxicillin+clarithromycin or metronidazole+omeprazole.…”
Section: Persistence Of H Pylori Infection After An Initial Positivementioning
confidence: 99%
“…Compared with reinfection, the time window for recrudescence is generally shorter. Recrudescence is generally considered as H pylori recurrence within 1 year after eradication, followed by the recurrence of H pylori –associated diseases in the short‐term . Patients with short‐term recurrence suffer from the risk of recurrence of these diseases.…”
Section: Introductionmentioning
confidence: 99%